Negotiating the “Maze”: SEN and the Transition From Lower Secondary Education in Austria - Pessl, Gabriele (2022)
Austrian students with special educational needs (SEN) face many obstacles in the transition from lower to upper secondary education. Using administrative data from national statistics, we analyse the trajectories of these students focusing on two questions: First, what is the impact of the former setting on further pathways for students from special schools compared with mainstream schooling? Second, can low‐threshold training or apprenticeship projects (the “transition system”) compensate for educational disadvantages in former school careers and serve as a “second chance” or do they reinforce exclusionary practices by perpetuating “special tracks”? Regarding the first question, our research findings confirm those from several studies conducted in other German‐speaking countries that show advantages for graduates from mainstream education compared to those from special schools, as they face a lower risk of institutional exclusion. In respect of the second question, at first glance, our findings differ from prior research results. Participating in the transition system is associated with a slight increase in participation in upper secondary education, some increase in employment, and an important reduction concerning inactivity. As revealed by a regression analysis controlling for socio‐demographic characteristics, participation in this system has a distinct integrative influence. We conclude by hypothesising that this is due to the structure of the Austrian transition system offering pathways back to mainstream educational systems and formally recognised educational qualifications.